Influence of allelic variations in relation to norepinephrine and mineralocorticoid receptors on psychopathic traits: a pilot study - Guillaume Durand (PeerJ, 2018)
Background Past findings support a relationship between abnormalities in the amygdala and the presence of psychopathic traits. Among other genes and biomarkers relevant to the amygdala, norepinephrine and mineralocorticoid receptors might both play a role in psychopathy due to their association with traits peripheral to psychopathy. The purpose is to examine if allelic variations in single nucleotide polymorphisms related to norepinephrine and mineralocorticoid receptors play a role in the display of psychopathic traits and executive functions. Methods Fifty-seven healthy participants from the community provided a saliva sample for SNP sampling of rs5522 and rs5569. Participants then completed the Psychopathic Personality Inventory–Short Form (PPI-SF) and the Tower of Hanoi. Results Allelic variations of both rs5522 and rs5569 were significant when compared to PPI-SF total score and the fearless dominance component of the PPI-SF. A significant result was also obtained between rs5522 and the number of moves needed to complete the 5-disk Tower of Hanoi. Conclusion This pilot study offers preliminary results regarding the effect of allelic variations in SNPs related to norepinephrine and mineralocorticoid receptors on the presence of psychopathic traits. Suggestions are provided to enhance the reliability and validity of a larger-scale study.